Association between chronotype and metabolic-associated fatty liver disease in employed adults: A longitudinal study in Southwestern China - Fu, Yao; Yu, Bin; Yang, Bo; Pan, Jia; Feng, Chuanteng; Jia, Peng; Zeng, Honglian; Yang, Shujuan (Chronobiology international, 2023)
The circadian system is an essential physiological regulator of mammals, and sleep chronotype may be associated with the risk of metabolic disorders. However, evidence regarding the role of sleep chronotype in the development of metabolic-associated fatty liver disease (MAFLD) is scarce, particularly in employed adults. We conducted a longitudinal study of 1,309 employed adults in Southwestern China with a five-year follow-up from 2017 to 2021. MAFLD was assessed by the presence of hepatic steatosis using abdominal ultrasonography, overweight/obese status, diabetes mellitus, metabolic dysregulation, or elevation of high-sensitivity C-reactive protein. Chronotype was assessed by the Morning and Evening Questionnaire-5 (MEQ-5). The logistic random effects model was applied to analyze the 5-year panel data to estimate the association between chronotype and MAFLD, and the potential effect modification of demographics on such association. The MAFLD prevalence of participants was 38.6% at baseline and showed an increasing trend during follow-up (p for trends < 0.05). Compared with morning chronotype, evening chronotype was positively associated with MAFLD (OR = 2.19, 95%CI: [1.09, 4.40]) after controlled for covariates. Age, sex, ethnicity, and educational level did not modify the association between chronotype and MAFLD. These findings suggest that improving circadian rhythms could reduce the risk of MAFLD and chronic disease burden among employed adults.